2018
DOI: 10.15761/jpp.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Health Professionals in the IDF

Abstract: Background: Demographic, professional, and emotional symptoms have been associated with higher risk for burnout reaction among health professionals. The current study focused on three groups of military health professionals: physicians, dentists, and mental health officers. The aims of this study included examining burnout indices characterizing three health professional groups, seeking associations between mental burnout subscales (job demands and social support), and testing the mediating impact of job deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This goes in line with several other studies that showed no relationship between gender and burnout. [12][13][14] On the contrary, metaanalysis of 183 studies conducted by Purvanova and Muros 15 showed that women are more likely to experience EE, while men were more likely to experience DP. In addition, several studies showed that women have a higher level of burnout compared to men.…”
Section: Discussion Burnoutmentioning
confidence: 98%
“…This goes in line with several other studies that showed no relationship between gender and burnout. [12][13][14] On the contrary, metaanalysis of 183 studies conducted by Purvanova and Muros 15 showed that women are more likely to experience EE, while men were more likely to experience DP. In addition, several studies showed that women have a higher level of burnout compared to men.…”
Section: Discussion Burnoutmentioning
confidence: 98%